Batriscenellus Jeannel (Coleoptera, Staphylinidae, Pselaphinae) redefined, with notes on the Chinese species - Yin, Zi-Wei; Li, Li-Zhen; Zhao, Mei-Jun (Zootaxa, 2011)
The genus Batriscenellus Jeannel is redefined, and its taxonomic placement discussed. The subgenera Scaioscenellus Jeannel, Batriscenellinus Nomura, and Nipponoscenellus Nomura are placed as synonyms of Batriscenellus, and the genus is divided into six species groups. Three eastern Chinese species, B. chinensis, B. femoralis, and B. pulcher, are described as new. The following new combinations are created: B. auritus (Löbl), B. satoi (Nomura) and B. subpalpicolus (Nomura), all moved from Batrisiella to Batriscenellus. New distributional records for B. orientalis and B. auritus in China are provided. Illustrations of major diagnostic characters are given for the new and the newly recorded Chinese species. An identification key to the species groups and to the Chinese species of Batriscenellus is given. A checklist of Batriscenellus is presented.